ANALISIS DESAIN BANTALAN CELANA UNTUK PENDERITA HEMOROID (AMBEIEN) - Muhammad Khafidh; Daniel Affandi; Miranti Dewi Pramaningtyas; Febrianti Nurul Hidayah (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Hemorrhoids are an anorectal disease due to dilation of the blood vessels around the anus. At a certain level, hemorrhoids often cause pain complaints experienced by some patients, especially during sitting. One of the solution is to use a special underpants in which it reduces the pain during sitting, and at the same time, provides comfort feel for other activities. Therefore, an underpants pad is important to be designed to achieve the aforementioned goals. In the present work, an optimum underpants pad is designed, manufactured, and tested to the patients. The optimum design of underpants pad is determined by a Computer Aided Engineering (CAE) simulation. Two parameters of the underpants pad is investigated, namely design and thickness. Three type of designs are varied, namely design 1, design 2, and design 3. While the thickness of 3, 5, and 7 mm are used. The results show that design B and thickness of 7 mm gives the lowest stress on the buttocks. Based on the simulation results, several products are manufactured and tested by the patients. The material of underpants pad is Polyurethane Foam (PUF). All patients determined that the product with design B, thickness of 5 mm, and density of 115 kg/cm3 is the best product.